Method for Determination of 55Fe in Radioactive Used Oil from Nuclear Power Plant - MA Lina1, 2, FAN Fuyou3, QIU Xiangping3, WANG Lusheng1, 2, DAI Xiongxin1, 2 (Yuanzineng kexue jishu)
55Fe is an important corresponding activation product during the operation of nuclear power plants. 55Fe may be present in the used oil required for main circuit mechanical equipment through cross-contaminating during maintenance activities-including change-out of oil in plant equipment or directing contacting with contaminated water. Currently, used oil from nuclear power plants is mainly stored temporarily at nuclear power sites and needs to be treated by volume reduction to achieve the goal of waste minimization. Evaluation of the content of the important difficult-to-measure beta-radionuclide 55Fe is necessary for the management and disposal of used oil. In response to the need for the measurement of 55Fe in used oil, a method was established for the analysis of 55Fe in used oil. 5 mg of Fe3+ was added to the used oil sample, mixed well and left for 1 h to ensure that the Fe3+ is in equilibrium with the 55Fe in the sample. The iron in the used oil sample was back-extracted to the liquid phase with 9 mol/L HCl, passed through AGMP-1 anion-exchange resin, and the resin column was then rinsed with 60 mL of 12 mol/L HCl followed 8 mL of 6 mol/L HCl to remove the potential interfering nuclides 63Ni, 60Co, 54Mn, and 51Cr. Iron was eluted from the anion resin using 3 mL of 0.1 mol/L HCl. For the potentially interfering nuclide 59Fe, which cannot be removed by chemical separation, a method for analyzing the liquid scintillation counting spectra of the 55Fe and 59Fe dual nuclides was established and verified. The verified results show that the method can accurately calculate the 59Fe overflowing into the 55Fe counting window. By testing three commercially available scintillation cocktails, the acidic sample media containing 55Fe mixed with Ultima GoldTM LLT has the lowest detection limit and highest counting efficiency for LSC measurements of 55Fe. After the eluate was measured for iron recovery by an X-ray fluorescence spectrometer, 0.6 mL 14.7 mol/L H3PO4 was added to form colourless complex with Fe3+. Then, 14 mL of Ultima GoldTM LLT was added and mixed with the sample. The sample was gently agitated and placed in darkness in the liquid scintillation counter tray, and the counting was started 20 h later to minimize the luminescence. The method was applied to measure 55Fe in the used oil, the potential interfering nuclides for 55Fe were eliminated by the AGMP-1 anion exchange resin, which the decontamination factors are greater than 105 for 63Ni, 54Mn, 51Cr, and 5651 for 60Co. The average recovery of iron is 71%±2%, and the minimum detectable activity concentration for 55Fe in used oil is 0.02 Bq/g for 10 g sample with accounting time of 1 h. The method was validated by using spiked samples, and the measured 55Fe results agree well with the expected 55Fe values within an acceptable deviation of −2.9%-6.0%.